Inflammatory mechanisms underlying early Alzheimer’s disease pathology: evidence from the aging rhesus macaque brain - Datta, Dibyadeep; Wang, Min; Arnsten, Amy F. T. (Frontiers in Cellular Neuroscience, 2026)
Inflammation plays a large role in the etiology of the late onset, sporadic form of Alzheimer’s disease (AD), yet these critical factors are not adequately modeled in mice where inflammatory mechanisms often differ widely from primates. In contrast, aging rhesus macaques offer a powerful translational model for investigating how advancing age and inflammation initiate early-stage pathology in sporadic AD, and for evaluating preventive therapeutic strategies. Unlike rodents, macaques possess highly developed association cortices with magnified calcium signaling, human-like inflammatory responses, and are naturally homozygous for ApoE-ε4—factors that together contribute to the spontaneous emergence of tau and amyloid pathology alongside cognitive decline. Critically, macaques allow the detection of early, soluble forms of hyperphosphorylated tau (pTau), including pT217Tau, which rapidly dephosphorylates postmortem and is rarely observable in human brain tissue outside of biopsies. New findings reveal that soluble pTau is neurotoxic and capable of propagating pathology across cortical networks, with elevated pT217Tau in plasma. Growing evidence points to age-related inflammatory signaling as a key driver of calcium dysregulation, which in turn promotes tau hyperphosphorylation, amyloid-β (Aβ) accumulation, synapse loss and autophagic degeneration. Both GCPII (glutamate carboxypeptidase II) and kynurenic acid inflammatory signaling have expanded roles in the primate association cortices that contribute to cognitive deficits. Pharmacological interventions in aged macaques demonstrate that targeting inflammation and restoring calcium homeostasis can significantly reduce pTau pathology with minimal side effects—highlighting a promising path for early intervention in AD.